Closeness to God, Spiritual Struggles, and Wellbeing in the First Year of College - Gilbertson, Madison Kawakami; Brady, Shannon T.; Ablorh, Tsotso; Logel, Christine; Schnitker, Sarah A. (Frontiers in Psychology, 2022)
Spirituality is an important, but oft-overlooked, aspect of the self that may affect college students’ well-being and belonging. Few studies have systematically examined closeness to God and spiritual struggles as predictors of college student well-being during early college, which is a critical window for identity development. Moreover, research exploring interactions between spiritual struggles and closeness to God in predicting well-being outcomes is scarce. We address these gaps in the literature with an analytic sample comprised of 839 first-year college participants who identify as religious. The results of correlational analyses and linear mixed effect models are presented. Closeness to God was associated with greater well-being and belonging, and spiritual struggles were associated with lower well-being and belonging. In exploratory analyses, a moderating effect of closeness to God on the relation between spiritual struggles and negative outcomes was observed. Implications for higher education and college student development are discussed.